2019
DOI: 10.1186/s12890-018-0755-9
|View full text |Cite
|
Sign up to set email alerts
|

Poor lung ultrasound score in shock patients admitted to the ICU is associated with worse outcome

Abstract: BackgroundThe lung ultrasound score has been regarded as a decent semiquantitative score to measure the lung aeration loss. The score has been proven to be valuable in diagnosing and monitoring lung pathology, but no studies have demonstrated its relationship to the outcome. We aimed to investigate the relationship between the lung ultrasound score and outcome in shock patients in the Intensive Care Unit.MethodsThe data were extracted from the SHOCK-ICU study, a 14-month prospective study of shock patients in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 35 publications
(33 reference statements)
5
56
0
1
Order By: Relevance
“…More recently, Zou et al [17] broadened the prognostic value of LUS score to include shock intensive care unit (ICU) patients, and showed that a modified LUS score may act as an independent risk factor for ICU mortality. These data on shock patients were confirmed by Yin et al [18] in a study involving 175 patients in which the LUS score correlated with 28-day mortality as well as the APACHE II score and lactate serum levels.…”
Section: Lung Ultrasound Score (Lus)supporting
confidence: 58%
“…More recently, Zou et al [17] broadened the prognostic value of LUS score to include shock intensive care unit (ICU) patients, and showed that a modified LUS score may act as an independent risk factor for ICU mortality. These data on shock patients were confirmed by Yin et al [18] in a study involving 175 patients in which the LUS score correlated with 28-day mortality as well as the APACHE II score and lactate serum levels.…”
Section: Lung Ultrasound Score (Lus)supporting
confidence: 58%
“…LUS scores (0-36, calculated by summing all 12 individual quadrant scores) are used to assess aeration changes, and a higher grade represents more serious aeration loss but is inapplicable for pneumothorax ( Figure 2) [24][25][26]. The scoring system is as follows: score 0, healthy lung, equidistant A-lines parallel to the sliding pleura; score 1, moderate aeration loss, no fewer than 3 dispersive B lines originated from the pleural cavity; score 2, serious aeration loss, presence of coalescent B lines with pleural irregularities; and score 3, absolute aeration loss, subpleural consolidation.…”
Section: Lung Ultrasound Examinationmentioning
confidence: 99%
“…A daily LAS assessment can be used to monitor of the respiratory disease. The LAS may guide fluid management in septic ARDS patients: in this setting, the LAS score variations are more sensitive than oxygenation in early detection of lung aeration deterioration due to fluid loading [ 32 34 ]. In patients with ARDS, the regional lung ultrasound score is strongly correlated with tissue density assessed with quantitative computed tomography (CT), and the increase in lung volume induced by positive end-expiratory pressure (PEEP) in patients with ARDS [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%